2016
DOI: 10.1186/s12877-016-0248-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic osteomyelitis increases long-term mortality risk in the elderly: a nationwide population-based cohort study

Abstract: BackgroundThe elderly are predisposed to chronic osteomyelitis because of the immunocompromised nature of aging and increasing number of chronic comorbidities. Chronic osteomyelitis may significantly affect the health of the elderly; however, its impact on long-term mortality remains unclear. We conceived this retrospective nationwide population-based cohort study to address this issue.MethodsWe identified 10,615 elderly patients (≥65 years) comprising 965 patients with chronic osteomyelitis and 9650 without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 17 publications
1
29
0
3
Order By: Relevance
“…A study about acute-care hospitalized elderly patients reported that C-reactive protein (CRP) ≥ 30 mg/l predicted mortality (OR: 3.72, 95% CI: 1.34–10.31) [ 18 ]. SA may result in subsequent osteomyelitis [ 15 ] or chronic SA, which may cause a chronic inflammation and increase long-term mortality [ 21 ]. A nationwide population-based cohort study reported that geriatric participants with chronic osteomyelitis had a significantly higher mortality risk than those without chronic osteomyelitis [incidence rate ratio (IRR): 2.29, 95% CI: 2.01–2.59] [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study about acute-care hospitalized elderly patients reported that C-reactive protein (CRP) ≥ 30 mg/l predicted mortality (OR: 3.72, 95% CI: 1.34–10.31) [ 18 ]. SA may result in subsequent osteomyelitis [ 15 ] or chronic SA, which may cause a chronic inflammation and increase long-term mortality [ 21 ]. A nationwide population-based cohort study reported that geriatric participants with chronic osteomyelitis had a significantly higher mortality risk than those without chronic osteomyelitis [incidence rate ratio (IRR): 2.29, 95% CI: 2.01–2.59] [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the geriatric population was 13.3% in Taiwan; however, it will rapidly grow to 20% by 2025 [2,3]. The growing geriatric population will contribute to a serious burden on the health care system because the elderly use more medical resources than their younger counterparts due to their multiple and complex comorbidities [3][4][5][6][7][8][9][10][11]. The statistics from the Taiwan National Health Insurance demonstrated that the geriatric population contributed to 38.5% of the total expenditures in 2015, and the proportion is still growing [12].…”
Section: Clinical Researchmentioning
confidence: 99%
“…4 The current approach to treat osteomyelitis is mainly antimicrobial and often intravenous and long-term, with surgical intervention in many cases to control infection. The causative pathogens in the majority of long bone osteomyelitis cases are biofilms of Staphylococcus aureus ; these microbes are bound to bone (Figure 1) in contrast to their planktonic (free-floating) counterparts.…”
Section: Introductionmentioning
confidence: 99%